المال الحرام وحكم الانتفاع به في المذهب المالكي - بليلة, أحلام; رقيق, عائشة; هزيل, روية (جامعة الوادي - University of Eloued, 2019)
إف ىذه ات١ذكرة تتناكؿ موضوع المال الحرام وحكم الانتفاع بو في المذىب المالكي الذم يعد ت٥الفة لأمر الشارع اتٟكيم ،فهو حجاب بتُ العبد كربو لا ينبغي للمسلم أف يقد عليو،حيث تهدؼ ىذه الدراسة إلى معرفة حقيقة ات١اؿ اتٟرا ك أقسامو ك التحلل منو كطرؽ التصرؼ بو،لذلك فما ىي الضوابط الشرعية التي يدكن ات ا خذىا عند اكتساب ىذا ات١اؿ؟ Abstract This memo deals with the subject of forbidden money and the ruling on using it in the Maliki school, which is a violation of the command of the wise street. It is a veil between the servant and his Lord. The Muslim should not submit it. This study aims at knowing the truth of the haraam wealth, So what are the legal rules that can be taken when this money is acquired
مذكرة ليسانس
Keywords: المال الحرام /المذهب المالكي; Argent interdit/École de pensée Maliki